Determining the feasibility of a codesigned and personalised intervention (Veg4Me) to improve vegetable intake in young adults living in rural Australian communities: protocol for a randomised controlled trial - Ralph Maddison; John C Mathers; Sarah A McNaughton; Lauren C Blekkenhorst; Katherine M Livingstone; Gavin Abbott; Laura Alston; Jonathan C Rawstorn; Eric O; Yuxin Zhang; Scott Barnett; Stephanie R Partridge; et al. (BMJ Open)
Introduction Diets low in vegetables are a main contributor to the health burden experienced by young adults in rural communities. Digital health interventions provide an accessible delivery model that can be personalised to meet the diverse preferences of young adults. A personalisable digital vegetable intake intervention (Veg4Me) was codesigned to meet the needs of young adults living in rural communities. This study will determine the feasibility of delivering a personalised Veg4Me programme and compare preliminary effects with a non-personalised Veg4Me (control).Methods and analysis A 12-week assessor-blinded, two-arm, parallel randomised controlled trial will be undertaken from August 2023 until April 2024. A total of 150 eligible and consenting young adults (18–35 years; eat<5 serves of vegetables/day; have an internet connected mobile device/computer) living in Loddon Campaspe or Colac Otway Shire in Victoria, Australia, will be randomised to receive 12 weeks of personalised (intervention) or non-personalised (control) support to increase vegetable intake via a free web application (app; Veg4Me). The primary outcome is feasibility (recruitment, participation and retention rates). Secondary outcomes are user engagement, usability and experience, as well as vegetable intake, eating habits and digital health equity. Process evaluation will be conducted in a subsample of participants using semistructured interviews. Descriptive statistics will be presented for the personalised and non-personalised groups at baseline and 12 weeks. Generalised linear models will be used to evaluate group differences in outcomes. Interviews will be transcribed and analysed thematically.Ethics and dissemination All procedures involving human subjects were approved by Deakin University’s Human Ethics Advisory Group—Health (HEAG-H 06_2023) on 6 March 2023. Dissemination events will be held in the City of Greater Bendigo and the Colac Otway Shire. Summaries of the results will be disseminated to participants via email. Results will be disseminated to the scientific community through peer-reviewed publications and conference presentations.Trial registration number Australia New Zealand Clinical Trials Registry, ACTRN12623000179639p, prospectively registered on 21 February 2023, according to the World Health Organizational Trial Registration Data Set. Universal Trial Number U1111-1284-9027.